Genetic Variation Putatively Associated with Mycobacterium tuberculosis Resistance to Perchlozone, a New Thiosemicarbazone: Clues from Whole Genome Sequencing and Implications for Treatment of Multidrug-Resistant Tuberculosis - Igor Mokrousov; Anna Vyazovaya; Gulnora Akhmedova; Natalia Solovieva; Eugeni Turkin; Viacheslav Zhuravlev (MDPI AG, 2020)
Perchlozone ([PCZ] 4-thioureido-iminomethylpyridinium perchlorate) is a new thiosemicarbazone approved for the treatment of multidrug-resistant tuberculosis (MDR-TB) in Russia and some other countries. The ethA and hadABC mutations may confer PCZ resistance. At the same time, ethA mutations are known to mediate resistance to ethionamide (ETH) and prothionamide (PTH). We aimed to study the genetic variation underlying Mycobacterium tuberculosis resistance to PCZ through whole genome sequencing (WGS) of consecutive isolates recovered during long-term treatment. This prospective study included patients admitted in 2018-2019 to the regional tuberculosis dispensary, Kaliningrad, Russia, whose treatment regimen included PCZ. Multiple M. tuberculosis isolates were recovered during PCZ treatment, and the bacterial DNA was subjected to WGS followed by bioinformatics analysis. We identified mutations in the genes putatively associated with PCZ resistance, ethA, and hadA. The most frequent one was a frameshift ethA 106 GA > G (seven of nine patients) and most of the other mutations were also likely present before PCZ treatment. In one patient, a frameshift mutation ethA 702 CT > C emerged after six months of PCZ treatment. A frequent presence of cross-resistance mutations to PCZ and ETH/PTH should be taken into consideration when PCZ is included in the treatment regimen of MDR-TB patients.